THE CLERGY-LAITY DIVIDE IN THE CHURCH - Mattam, Joseph (Asian Horizons, 2015)
This short article shows that the clergy-laity divide that has come to characterize the Church for many centuries does not have its origin in Jesus. Jesus’ attitude to ‘priests’ was rather negative as we can gather from the story of the Good Samaritan; he does not use the term ‘priest’ except in this story and when telling leprosy patients to show themselves to the Jewish priests. The claim that just before his death Jesus ordained ‘priests’ just does not have any foundation in the NT. The normally proffered arguments that the Eucharist needs an ordained priest and the sacrament of Confession needs a priest are disproved by the practice of the early Church where the Eucharist was held in the homes presided over by the head of the family, and the sacrament of Confession was not known in the first century Church. Whereas, in all the four Gospels, Jesus speaks about the kind of leaders he wanted to leave behind — they were to be different from the leaders in the world; they had to be servants and were not even to be called master or father, but were to be brothers/sisters to one another. Jesus showed by the foot washing the kind of leaders he wanted. The leaders in the Apostolic Church were not priests; they were what we have come to call ‘lay people’, not clerical figures at all. Hence this article pleads for a return to what Jesus wanted: a community of brothers/sisters where no one is superior or inferior but with distinctfunctions which do not make one superior, or more ‘reverend’; each member is responsible and respectable; all the offices of services should be open to every member who is willing to serve the community. It is hoped that such a change is possible.